Ameliorative Effect of Chrysin on Adenine-Induced Chronic Kidney Disease in Rats - Ali, Badreldin H.; Adham, Sirin A.; Al Za’abi, Mohammed; Waly, Mostafa I.; Yasin, Javed; Nemmar, Abderrahim; Schupp, Nicole (PLOS ONE, 2015)
Chrysin (5, 7- dihydroxyflavone) is a flavonoid with several pharmacological properties that include antioxidant, anti-inflammatory and antiapoptotic activities. in this work, we investigated some effects of three graded oral doses of chrysin (10, 50 and 250 mg/kg) on kidney structure and function in rats with experimental chronic renal disease (CKD) induced by adenine (0.25% w/w in feed for 35 days), which is known to involve inflammation and oxidative stress. Using several indices in plasma, urine and kidney homogenates, adenine was found to impair kidney function as it lowered creatinine clearance and increased plasma concentrations of creatinine, urea, neutrophil gelatinase-associated lipocalin and N-Acetyl-beta-D-glucosaminidase activity. Furthermore, it raised plasma concentrations of the uremic toxin indoxyl sulfate, some inflammatory cytokines and urinary albumin concentration. Renal morphology was severely damaged and histopathological markers of inflammation and fibrosis were especially increased. In renal homogenates, antioxidant indices, including superoxide dismutase and catalase activities, total antioxidant capacity and reduced glutathione were all adversely affected. Most of these adenine – induced actions were moderately and dose -dependently mitigated by chrysin, especially at the highest dose. Chrysin did not cause any overt adverse effect on the treated rats. The results suggest that different doses of chrysin produce variable salutary effects against adenine-induced CKD in rats, and that, pending further pharmacological and toxicological studies, its usability as a possible ameliorative agent in human CKD should be considered.